THE ROLE OF CLOUD-BASED ACCOUNTING SYSTEMS IN ENHANCING FINANCIAL INFORMATION QUALITY - Franco Benony Limba; Shella Gilby Sapulette; Alend Talla (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the role of cloud-based accounting systems in improving the quality of financial information through a literature review approach. The development of cloud technology has significantly transformed accounting practices, particularly in terms of efficiency, transparency, and accuracy of financial reporting. Through a literature review from various academic sources, this study identified that the implementation of cloud-based accounting systems can improve the relevance, reliability, timeliness, and comparability of financial information. Furthermore, these systems enable real-time access to accounting data, strengthen internal controls, and support strategic decision-making based on more accurate data. However, challenges such as data security issues, implementation costs, and resistance to change were also identified as factors that may impact the effectiveness of this technology implementation. Overall, the results of this study confirm that cloud-based accounting systems make a substantial contribution to improving the quality of financial information, although their success depends heavily on the organization's readiness to manage technological change and the associated risks.